Heart–lung transplant in congenitally corrected transposition of the great arteries and dextrocardia patient. (February 2021) - El-Sayed Ahmed, Magdy M; Thomas, Mathew; Makey, Ian A; Martin, Archer K; Erasmus, David B; Sareyyupoglu, Basar; Landolfo, Kevin P; Pham, Si M
A 53-year-old male patient was presented to our institution with the clinical picture of biventricular failure. The echocardiogram revealed congenitally corrected transposition of the great arteries, dextrocardia with situs solitus, atrioventricular discordance and ventriculoatrial discordance, severe systemic and mitral valves regurgitation, and severe pulmonary hypertension (mean pulmonary artery pressure: 51 mm Hg). He underwent heart–lung transplant. He was discharged on postoperative day 25 with left ventricular ejection fraction of 60%–65%, and with oxygen independency.